2021
DOI: 10.1002/ece3.7856
|View full text |Cite
|
Sign up to set email alerts
|

Asexual reproduction and vegetative growth of Bionectria ochroleuca in response to temperature and photoperiod

Abstract: Phenotypic plasticity is the ability of a given genotype to produce different phenotypes in various environments (Holloway, 2002) and is a fundamental characteristic of all organisms, enabling adaptation to various environments (Slepecky & Starmer, 2009). The molecular basis of phenotypic plasticity is differential gene expression triggered by environmental changes (Alvarez et al., 2015;Gibson, 2008). Such regulation includes early signal responses, signal transduction, and gene expression regulation (Lengeler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 110 publications
1
3
0
Order By: Relevance
“…Statistical analyses indicated an overall trade-off between the two variables, i.e. IVGR and SP, at the species level, supporting previous studies on Bionectria ochroleuca which, again, has been reported as a fungal plant pathogen, an endophyte in plant tissues or as a free-living form rather than a strict saprobe [ 44 ]. However, statistical analyses conducted separately on data of either P. gigantea from Norway spruce or from Scots pine pointed to a clear and significant trade-off between the two variables only with reference to isolates collected from Norway spruce.…”
Section: Discussionsupporting
confidence: 83%
“…Statistical analyses indicated an overall trade-off between the two variables, i.e. IVGR and SP, at the species level, supporting previous studies on Bionectria ochroleuca which, again, has been reported as a fungal plant pathogen, an endophyte in plant tissues or as a free-living form rather than a strict saprobe [ 44 ]. However, statistical analyses conducted separately on data of either P. gigantea from Norway spruce or from Scots pine pointed to a clear and significant trade-off between the two variables only with reference to isolates collected from Norway spruce.…”
Section: Discussionsupporting
confidence: 83%
“…Symptomatic plant parts were first cut into small pieces and placed on potato dextrose agar (PDA; streptomycin: 40 µg ml −1 , China). Fungal colonies were purified to individual isolates in order to separate the potential pathogenic strains (Zheng et al, 2021). We extracted total genomic DNA for each of the fungal isolates with the help of Qiagen Plant DNeasy kits (Qiagen, Hilden, Germany).…”
Section: Assessment Of Fungal Disease Of V Mangachapoimentioning
confidence: 99%
“…A 30 µL PCR reaction mixture included the following: 15 µL of Phusion Master Mix (2×), 10 µL of DNA template, 3 µL of primer, and 2 µL of dd H 2 O. The PCR conditions were as following: a hot start at 98 • C for 1 min; then 30 cycles of 98 • C for 30 s, 55 • C for 30 s and 72 • C for 30 s; and a final extension at 72 • C for 5 min (Zheng et al, 2021)…”
Section: Assessment Of Fungal Disease Of V Mangachapoimentioning
confidence: 99%
“…Organisms frequently exhibit functional tradeoffs. For example, tradeoffs have been observed in fungi between growth and enzymatic activity (Zheng et al, 2020), between growth and reproduction [ 29 , 30 ] and between growth and defense [ 31 ]. Still other tradeoffs occur because organisms frequently cannot excel along the entire length of an environmental gradient.…”
Section: Introductionmentioning
confidence: 99%